2001
DOI: 10.2310/6650.2001.33901
|View full text |Cite
|
Sign up to set email alerts
|

Association of Traditional Risk Factors with Coronary Calcification in Persons with a Family History of Premature Coronary Heart Disease: The Study of the Inherited Risk of Coronary Atherosclerosis

Abstract: In a cohort of subjects specifically selected for the characteristic of a family history of premature CHD, traditional risk factors accounted for less than one-third of the variation in CAC, and the most important predictors of CAC after age were plasma triglycerides. This supports the opinion that other inherited risk factors have important effects on the variation in coronary atherosclerosis and that the strategy of using EBT to phenotype clinically asymptomatic subjects with regard to coronary atheroscleros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
(40 reference statements)
0
26
0
Order By: Relevance
“…In the Study of the Inherited Risk for Coronary Atherosclerosis (SIRCA), 52% of women and 78% of men with a family history of premature CHD and without CHD or diabetes had a positive coronary calcium score. 9 The mean age of men in SIRCA was 45 y and the mean age of women was 50 y. These findings suggest a high prevalence of subclinical CAD in healthy younger individuals with a family history of premature CHD.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the Study of the Inherited Risk for Coronary Atherosclerosis (SIRCA), 52% of women and 78% of men with a family history of premature CHD and without CHD or diabetes had a positive coronary calcium score. 9 The mean age of men in SIRCA was 45 y and the mean age of women was 50 y. These findings suggest a high prevalence of subclinical CAD in healthy younger individuals with a family history of premature CHD.…”
Section: Discussionmentioning
confidence: 60%
“…In SIRCA, traditional risk factors accounted for less than one-third of the variations in coronary calcium. 9 Akosah et al 12 evaluated 222 younger patients admitted to the hospital with an acute myocardial infarction and found that most had few traditional CV risk factors. Only 17% would have been predicted as being at high risk based solely on their Framingham risk score, and almost 75% would not have qualified for lipid-lowering therapy based on current lipid-lowering guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…A positive relationship between VC and serum total and LDL cholesterol and triglyceride levels was shown in the general population (149,152,153). A small Japanese study found that rapid progression of coronary artery calcification was associated with high triglyceride and low HDL cholesterol concentrations in longterm hemodialysis patients (154).…”
Section: Pathophysiology Of Cvd In Ckdmentioning
confidence: 99%
“…The study designs and initial fi ndings of subjects were previously reported from HHDL ( 14 ) and SIRCA ( 16 ). Subjects identifi ed with the G26S variant were compared with age-and sex-matched control subjects from both SIRCA and HHDL.…”
Section: Human Subjectsmentioning
confidence: 99%